Histological Outcomes and Predictive Value of Faecal Markers in Moderately to Severely Active Ulcerative Colitis Patients Receiving Infliximab. (25th May 2016) - Magro, Fernando; Lopes, Susana Isabel; Lopes, Joanne; Portela, Francisco; Cotter, José; Lopes, Sandra; Moreira, Maria João; Lago, Paula; Peixe, Paula; Albuquerque, Andreia; Rodrigues, Susana; Silva, Mário Rui; et al.
Abstract: Background and Aims: Histological healing has emerged as a promising therapeutic goal in ulcerative colitis. This is especially important in the context of biological therapies. The objectives of the present study were to investigate the ability of infliximab to induce histological remission in ulcerative colitis [UC] patients and to explore the utility of faecal calprotectin and lactoferrin in predicting histological activity. Methods: Multi-centre, single-cohort, open-label, 52-week trial including moderately to severely biological-naïve UC patients receiving intravenous infliximab [5mg/kg]. The primary outcome was the proportion of patients with histological remission [Geboes index ≤ 3.0] after 8 weeks of treatment, scored by two independent pathologists. Results: Twenty patients were included. The rate of histological remission increased from 5% at baseline to 15% and 35% at Week 8 and Week 52, respectively. At Week 8, 40% of patients were in clinical remission [Mayo ≤ 2] and 45% achieved mucosal healing [Mayo endoscopy subscore 0–1]. At Week 52, 25% of patients had clinical, endoscopic and histological remission. Faecal calprotectin and lactoferrin showed the highest correlation with histological activity at Week 8 (area under the curve [AUC] 94%, p = 0.017; and 96%, p = 0.013, respectively) and both markers revealed an excellent positive predictive value for this outcome at this time point [100%, p = 0.017; and 94%, p = 0.013, respectively]. Conclusions: Infliximab was able to induce histological remission. There was a good agreement between histology and faecal biomarkers. Faecal calprotectin and lactoferrin were good predictors of histological remission. Our data support inclusion of histology as a treatment target complementary to endoscopy in clinical trials when evaluating therapeutic response in UC.